Moluscos terrestres exóticos y primera cita de la familia Punctidae (Moll.:Gastr.:Pulm.) y de su especie Paralaoma servilis para Cuba - Maceira, David (2013)
Checklists of 52 exotic land molluscs for Cuba and eight native Cuban land snail occurring in others countries are presented. The first record of the micromollusc Paralaoma servilis (Shuttleworth, 1852) and its family Punctidae from Cuba is also added.